Motivating First-Generation Factory Employees: A Case Study of the Garment Industry in Myanmar - Kojima, Eitaro; Ohno, Akihiko (UI Scholars Hub, 2022)
Research Aims: This study investigates how to foster and motivate factory employees at the onset of industrialisation. Design/methodology/approach: A total of 728 employees of the garment sector in Myanmar were surveyed using a structured questionnaire. Research Findings: The results of this study indicate 1) that employees’ maladaptation to factory discipline leads to workplace stress and fuels employees’ counter-productive behaviour and 2) that employees who perceive benevolence from the factory manager take on pro-organizational (vs counter-productive) behaviour based on social exchange rooted in indigenous patron-client ties. Theoretical Contribution/Originality: This study discusses the singular aspects of human resource management (HRM) at the onset of industrialisation. The cause of workplace stress differs from what is widely claimed in industrialised societies. Organisational commitment is deeply affected by cultural settings. Managerial Implications in the South East Asian Context: This study offers insights for cultivating and motivating factory employees hailing from indigenous societies. Moreover, HRM practices based on patron-client ties that persist in southeast Asian societies can be effective measures to enhance organisational commitment. Research Limitations & Implications: The current study does not cover either white-collar or skilled employees in the capital-intensive industry.